Effective Learning Activities To Improve Early Childhood Cognitive Development - Amalia, Eka Rizki; Khoiriyati, Salis (Al-Athfal: Jurnal Pendidikan Anak, 2018)
Children in their critical period or commonly known as golden age are in their optimal stage where they grow and develop rapidly and absorb anything which is exposed to them. Therefore, this is the period when the parents and older person have the opportunity to give the appropriate influence thus the children’s development can result optimally in all areas. The first and most critical aspect is the cognitive ability. Cognitive ability can become the basis of all input to be processed in the children’s mind, thus its development will affect the children’s ability to absorb anything from their surroundings. This article will discuss about learning activities which are effective to improve early childhood cognitive development. The discussion reveals that children in their early age are more active and effective in activities which are designed as games and will result more in their development as they are engaged in social interaction. Some games are proposed as alternatives for the children and parents to conduct and to be involved in.